Properties of Thermal Conductivity Hybrid Epoxy Resin Composite Reinforced Natural Fiber as Alternative Insulator Material - Ketut Suarsana; DNK Putra Negara; Igpagus Suryawan (Diponegoro University, 2022)
The properties of composite materials are highly dependent on the constituents used as reinforcement such as natural fibers with a matrix. This research was conducted to determine the effect of chemical solution treatment of NaOH and Silane coupling agent on fiber with concentration on thermal conductivity properties. The research involved processing fiber from nettle plant by decortication to obtain a single fiber. The hybrid composite process uses the hand lay-up molding method. The fibers were treated with a chemical solution of NaOH and Silane at concentrations of: 3 and 6% for 2 hours, had a length of 5 mm, and in random orientation. The ratio of the nettle fiber reinforced resin matrix to the weight ratio of natural fibers was 10, 15, 20 and 25%. The results obtained that the highest thermal conductivity properties with a fiber composition of 25% in the chemical solution treatment of 6% Silane of 0.1995 Watt/moK. On the other hand, the lowest with a composition of 10% natural fiber with 3% NaOH treatment of 0.1099 Watt/moK. The low thermal conductivity of hybrid composites can be applied as an insulator